PENERAPAN KEBIJAKAN PENEGAKAN HUKUM TERHADAP KASUS-KASUS HUKUM TERKAIT PEMBERITAAN PERS DI INDONESIA - Pri Pambudi Teguh (Universitas Nasional, 2021)
This research is based on the existence of a disagreement on the application of press law and a lack of understanding of law enforcement officials regarding legal cases related to press coverage. This kind of situation must be guarded and extended to other law enforcement officials so that law enforcement efforts do not have to conflict with the will of the people in maintaining and maintaining press freedom that has been guaranteed by the UUD 1945 and its amendments. By using juridical methods of format and approaches to several theories, namely Grand theory, Middle Range Theory and Applied Theory (as Grand Theory uses Materiel Law State Theory, Middle-Range Theory uses Development Law Theory and Applied Theory uses Criminal Law Political Theory supported by Systems Theory. Criminal Justice), this study aims to determine the application of law enforcement policies to legal cases related to press coverage in Indonesia. The conclusions obtained are as follows: 1. Law No. 40 of 1999 concerning the Press is not a lex specialis against the Criminal Code (KUHP), therefore the Criminal Code remains valid in enforcing press offenses, while civil charges resulting from press coverage can use Article 1365 and / or Article 1367 of the Civil Code. 2. Law enforcement policies in the press sector are formulated and implemented in a balanced manner between the need to maintain press freedom based on the 1945 Constitution and legal guarantees of individual rights to press coverage.